Dizelsko-motomi vlakovi za prigradski promet - Zavada, Josip (Promet - Traffic&Transportation, 2012)
The paper furnishes a review of different designs of diesel motor trains, and lists their manufacturers and users. The author discusses the basic properties of trains designed for suburban traffic and indicates the possible trends of future development. Individual practical propositions are committed to analysis regarding drive, transmission and operation of diesel motor trains. Furthermore, the criteria for the option of the diesel motor train in suburban traffic are reviewed.